Transcriptional regulation of virulence and stress adaptation in Akanthomyces attenuatus JEF-147 during mite pathogenesis - Yejin Choi; Suyeon Jin; Gahyeon Song; Ganghwan Kim; Mi Rong Lee; Jae Su Kim (Journal of Invertebrate Pathology, 2026)

The Predictability of Ocean Environments that Contributed to the 2020/21 Extreme Cold Events in China: 2020/21 La Niña and 2020 Arctic Sea Ice Loss - Fei Zheng; Ji-Ping Liu; Xiang-Hui Fang; Mi-Rong Song; Chao-Yuan Yang; Yuan Yuan; Ke-Xin Li; Ji Wang; Jiang Zhu (Advances in Atmospheric Sciences, 2022)
Several consecutive extreme cold events impacted China during the first half of winter 2020/21, breaking the low-temperature records in many cities. How to make accurate climate predictions of extreme cold events is still an urgent issue. The synergistic effect of the warm Arctic and cold tropical Pacific has been demonstrated to intensify the intrusions of cold air from polar regions into middle-high latitudes, further influencing the cold conditions in China. However, climate models failed to predict these two ocean environments at expected lead times. Most seasonal climate forecasts only predicted the 2020/21 La Niña after the signal had already become apparent and significantly underestimated the observed Arctic sea ice loss in autumn 2020 with a 1–2 month advancement. In this work, the corresponding physical factors that may help improve the accuracy of seasonal climate predictions are further explored. For the 2020/21 La Niña prediction, through sensitivity experiments involving different atmospheric–oceanic initial conditions, the predominant southeasterly wind anomalies over the equatorial Pacific in spring of 2020 are diagnosed to play an irreplaceable role in triggering this cold event. A reasonable inclusion of atmospheric surface winds into the initialization will help the model predict La Niña development from the early spring of 2020. For predicting the Arctic sea ice loss in autumn 2020, an anomalously cyclonic circulation from the central Arctic Ocean predicted by the model, which swept abnormally hot air over Siberia into the Arctic Ocean, is recognized as an important contributor to successfully predicting the minimum Arctic sea ice extent.

Design, synthesis, and antifungal activity evaluation of novel 2-cyano-5-oxopentanoic acid derivatives as potential succinate dehydrogenase inhibitors - Xue-song Wang; Xiao-rong Tang; Mi-jun Peng; Yong-zhan Mai (Medicinal Chemistry Research, 2022)

Sulfuretin induces osteoblast differentiation through activation of TGF-β signaling - No-Joon Song; So-Mi Kwon; Suji Kim; Hyang-Jin Yoon; Cho-Rong Seo; Byunghyun Jang; Seo-Hyuk Chang; Jin-Mo Ku; Jeong-Soo Lee; Ki-Moon Park; Joung-Woo Hong; Geun Hyung Kim; et al. (Molecular and Cellular Biochemistry, 2015)